Revisiting the Galactic X-Ray Binary MAXI J1631–479: Implications for High Inclination and a Massive Black Hole - Sandeep K. Rout; Santosh Vadawale; Javier Garćia; Riley Connors (The Astrophysical Journal, 2023)
X-ray spectroscopy of Galactic black hole binaries serves as a powerful tool to gain an overall understanding of the system. Not only can the properties of the accretion disk be studied in detail, the fundamental properties of the black hole such as spin and mass can also be measured. In this work we carry out a comprehensive spectral analysis of the X-ray binary MAXI J1631–479 using data from NICER and NuSTAR observatories. We trace the evolution of the accretion disk properties, such as density, ionization, and Fe abundance, as the source transitions from a disk-dominated soft state to a power-law-dominated hard intermediate state. As expected the disc ionization increased with hardness while the density and abundance (at solar values) remained unchanged. We provide strong constraints on the spin of the black hole (a > 0.996) and the inclination of the inner disk (50°–70°). We also use the soft-state NICER observations to constrain the black hole mass using distance estimates from optical observations. We find the probable mass of the black hole to be much higher than its X-ray binary counterparts with a conservative lower limit of 15 ${M}_{\odot }$ at 4.5 kpc.